Differential Germination and Growth Response to Temperature of Three Ambrosia Weed Species—Implications for Future Spread - Yair, Yifat; Goldwasser, Yaakov; Sibony, Moshe; Eizenberg, Hanan; Rubin, Baruch (Frontiers in Agronomy, 2020)
Three main Ambrosia species (Ragweed) grow in Israel; the most abundant invasive Ambrosia confertiflora DC, whereas A. artemisiifolia L. and A. tenuifolia Spreng., are of restricted distribution. The present research was aimed to study the effect of temperatures regimes on the development and growth of these Ambrosia species, to elucidate the environmental conditions and plant traits that affect their growth and infestation patterns. All three Ambrosia species germinate best in light from the soil surface with no prerequisite of a stratification period. A. confertiflora seed emergence is inhibited at high temperature regimes (28/34°C). A. artemisiifolia at low temperature regimes (10/16°C), while A. tenuifolia is less affected by the temperature regimes. A. confertiflora plant height increases with increasing temperatures, and at lower temperatures develops a rosette. Root and rhizome biomass were less affected by the different temperatures regimes; A. artemisiifolia aboveground mass was not affected by temperature regimes while A. tenuifolia aboveground mass was reduced only at lower temperatures. A. confertiflora fast invasion and establishment are due to the combined effects of prolific seed dispersal, rapid sprouting and growth, and its phenotypic plasticity.